PENENTUAN pH, CHEMICAL OXYGEN DEMAND DAN TOTAL SUSPENDED SOLID PADA KOLAM LIMBAH CAIR PABRIK KELAPA SAWIT - Syafrinal, Syafrinal; Samah, Selfa Dewati; Putri, Melysa; Fatmawati, Fatmawati; Januarti, Ria (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2023)
Palm oil mill effluent can pollute the environment and endanger human health. Test parameters that can indicate the quality of palm oil mill effluent are pH, Chemical Oxygen Demand, and Total Suspended Solid. The purpose of this study is to determine the pH using pH meter, COD and TSS values using spektrofotometer UV – Vis in each palm oil mill effluent pond before discharging into the river so as not to pollute the environment. The results of three weeks of testing showed that the pH value of the palm oil mill effluent pond tended to increase from the fat fit pond to the outlet of pond V while the COD and TSS values tended to decrease from the fat fit pond to the outlet of pond V. The pH value of the waste discharged into the river is in the range of 6-9, the COD value is below 350 mg/L and TSS is below 250 mg/L. The results obtained are in accordance with the regulation of the Minister of Environment Number 5 of 2014.  The resulting palm oil mill effluent is safe to be discharged into the river.